The dispersal capacity of Mollusca—a test on the South Azorean Seamount Chain - Caballero Herrera, José Antonio; Hoffman, Leon; Freiwald, André; Gofas, Serge (Springer, 2023)
This study investigates the molluscan fauna of the South Azorean Seamount Chain (SASC), which comprises several seamounts culminating in 300–1600 m depth, separated by distances less than 200 km. Material was collected mainly by dredging and comprises mostly empty shells. A total of over 111,000 shells representing at least 439 species (409 identified) was collected. Larval development was inferred from protoconch morphology, and the assemblage comprises species with planktotrophic larvae, with non-feeding planktonic larva, and with lecithotrophic larvae with direct development. The direct developers are more prevalent among species endemic to the SASC in the upper bathyal part (300–800 m) of the seamounts, whereas most planktotrophic species are shared with the Lusitanian seamounts and/or the European mainland. Nevertheless, there are notable exceptions to this trend, where species with non-planktotrophic larvae are also widespread, and a large proportion of the species with non-feeding planktonic larvae are shared with Eastern and/or Western Atlantic. Level of endemism of Mollusca is high within the SASC (22.5% overall, 35.8% considering only the interval < 800 m) and even higher (32.6% overall) when considering together the SASC and the Azores. The generic composition and large set of overlapping fauna suggest a strong relation to the temperate Eastern Atlantic, whereas only 19% of the species are shared with the Western Atlantic.
Keywords: Larvas - Desarrollo; Moluscos - Larvas - Distribución geográfica; Zona abisal - Azores; Larval development; Seamount; Deep sea; Marine biogeography; North Atlantic